Pengembangan Game Edukasi Berbasis Android untuk Meningkatkan Kemampuan Pembelajaran Bahasa Inggris Siswa Sekolah Dasar (Studi Kasus: SD Negeri 8 Kedondong) - Agustina Agustina; Suyono Suyono; Lilis Tri Handayani (JELTec (Journal of Learning Technology), 2025)
Learning English is an important component in the global education curriculum, considering its role as an international language that supports cross-cultural communication and scientific fields. Likewise, the development of information and communication technology has had a significant impact on various aspects of life, including in the field of education. In this digital era, traditional learning methods are often considered less effective in attracting students' interest, especially in learning foreign languages ​​such as English. With more and more young people using mobile devices, there is a huge opportunity to leverage technology to create more engaging and interactive learning experiences. This research discusses the development and implementation of educational games specifically designed for English language learning. This research also aims to design and develop an English language learning application based on educational games on the Android platform. The method used in this research is the System Development Life Cycle (SDLC) method, a systematic approach to designing, developing and implementing systems. It is hoped that this English learning educational game application can improve students' ability to learn and understand English.